2021
DOI: 10.1080/16089677.2021.1877443
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a face-to-face peer-support intervention on adults with type 2 diabetes: a cluster-randomised trial

Abstract: To establish the impact of a face-to-face peer-support intervention on adults with type 2 diabetes in South Africa. Methods: A cluster randomised controlled trial was conducted involving 288 adults with type 2 diabetes from six communities in the Free State province. Individuals (n = 141) in three communities were randomly allocated to the intervention group, and individuals (n = 147) in another three communities were randomly allocated to the control group. Trained community health workers led monthly group s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…However, the diversity in study designs, contexts and type of interventions implemented should be considered in interpreting findings. Put together, these findings support previous literature in sub-Saharan Africa on clinical outcomes of peer interventions [ 25 , 28 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 89%
“…However, the diversity in study designs, contexts and type of interventions implemented should be considered in interpreting findings. Put together, these findings support previous literature in sub-Saharan Africa on clinical outcomes of peer interventions [ 25 , 28 , 62 , 63 ].…”
Section: Discussionsupporting
confidence: 89%
“…[2][3][4][5][6][7] In fact, several systematic reviews and meta-analyses have found peer support interventions in diabetes to be associated with improvements in clinical, self-management, and psychological outcomes. 5,[8][9][10][11][12] Peer support models targeting adults with T2D have recruited predominantly from primary care clinics or community health centres, 3,[13][14][15][16][17][18][19] However, it is T2D patients from specialty care settings who are at highest risk and with the greatest need as they are more likely to be newly diagnosed requiring additional support; poorly controlled over a longer period of time, and diagnosed with multiple and complex chronic conditions. For this reason, the specialty care setting may be the point where peer support can have the greatest impact and patients can derive the most benefit.…”
Section: Introductionmentioning
confidence: 99%